Pengaruh Kompensasi, Kompetensi, dan Disiplin Kerja Terhadap Kinerja Guru Di SMP Negeri 1 Tembelang - Rina Amelia Putri; Siti Nur Qomariyah (Management and Education Journal, 2026)
This study aims to analyze the effect of compensation, competence, and work discipline on teacher performance at SMP Negeri 1 Tembelang. The research used a quantitative method with an associative approach. Data were collected through Likert-scale questionnaires (1–4) from 46 teachers and analyzed using SmartPLS 4. The results show that compensation (coefficient 0.224; p-value 0.016) and work discipline (coefficient 0.481; p-value 0.000) have a positive and significant effect on teacher performance. Meanwhile, competence has a positive but insignificant effect (coefficient 0.625; p-value 0.074). Simultaneously, these variables explain 72.6% of the variance in teacher performance (R-Square = 0.726). The findings indicate that teacher performance improvement is more influenced by compensation and work discipline than competence.